Are dietary interventions with a behaviour change theoretical framework effective in changing dietary patterns? A systematic review - Deirdre Timlin; Jacqueline M. McCormack; Maeve Kerr; Laura Keaver; Ellen E. A. Simpson (BMC, 2020)
Abstract Background The term 'whole dietary pattern' can be defined as the quantity, frequency, variety and combination of different foods and drinks typically consumed and a growing body of research supports the role of whole dietary patterns in influencing the risk of non-communicable diseases. For example, the 'Mediterranean diet', which compared to the typical Western diet is rich in fruits and vegetables, whole grains, and oily fish, is associated with reduced risk of cardiovascular disease and cancer. Social Cognition Models provide a basis for understanding the determinants of behaviour and are made up of behavioural constructs that interventions target to change dietary behaviour. The aim of this systematic review was to provide a comprehensive assessment of the effectiveness and use of psychological theory in dietary interventions that promote a whole dietary pattern. Methods We undertook a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis to synthesize quantitative research studies found in Embase, Medline, PsycInfo, CINAHL and Web of Science. The studies included were randomised and non-randomised trials published in English, involving the implementation of a whole dietary pattern using a Social Cognition Model to facilitate this. Two independent reviewers searched the articles and extracted data from the articles. The quality of the articles was evaluated using Black and Down quality checklist and Theory Coding Scheme. Results Nine intervention studies met the criteria for inclusion. Data from studies reporting on individual food group scores indicated that dietary scores improved for at least one food group. Overall, studies reported a moderate application of the theory coding scheme, with poor reporting on fidelity. Conclusion To our knowledge, this is the first review to investigate psychological theory driven interventions to promote whole dietary patterns. This review found mixed results for the effectiveness of using psychological theory to promote whole dietary pattern consumption. However, the studies in this review scored mostly moderate on the theory coding scheme suggesting studies are not rigorously applying theory to intervention design. Few studies reported high on treatment fidelity, therefore, translation of research interventions into practice may further impact on effectiveness of intervention. Further research is needed to identify which behaviour change theory and techniques are most salient in dietary interventions.